SIMULTANEOUS-OPTIMIZATION OF CHEMICAL FLOWSHOP SEQUENCING AND TOPOLOGY USING GENETIC ALGORITHMS - Cartwright, H; Long, R (1993)
Scheduling heuristics are of considerable practical importance and, accordingly, have been studied using a variety of methods. Such heuristics commonly assume a flowshop of fixed serial topology, but this assumption seriously restricts the theoretical efficiency of the flowshop. In this paper we show that both flowshop chemical feedorder and the topology of the flowshop itself can be simultaneously refined using genetic algorithms. Because of the implicit parallelism of genetic algorithms, the method scales up readily to flowshops of industrial complexity. © 1993 American Chemical Society.